1983
DOI: 10.1007/bf00137292
|View full text |Cite
|
Sign up to set email alerts
|

Real education in non-real time: The use of electronic message systems for instruction

Abstract: Educationin different communication media takes place with functional differences that have consequences for the course of instructional interaction.In this paper, we examine instructional interaction among people using a computer-based electronic message system, contrasting it with conventional face-to-face discussion in a college level class. Interaction via the non-real time message system contained multiple "threads of discourse," a higher proportion of student turns to teacher turns, and other deviations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 4 publications
(4 reference statements)
5
25
0
1
Order By: Relevance
“…Our interview data support observations made by other researchers that listservs have the potential to enhance communication because they are independent of the constraints of place and time in traditional face-to-face settings (Althaus, 1997;Harasim, 1987;Quinn, Mehan, Levin, & Black, 1983).…”
Section: Research Question 2: What Are the Factors That Sustain Knowlsupporting
confidence: 68%
“…Our interview data support observations made by other researchers that listservs have the potential to enhance communication because they are independent of the constraints of place and time in traditional face-to-face settings (Althaus, 1997;Harasim, 1987;Quinn, Mehan, Levin, & Black, 1983).…”
Section: Research Question 2: What Are the Factors That Sustain Knowlsupporting
confidence: 68%
“…This ability may afford users enhanced opportunities for selective self-presentation, rendering qualitatively different interpersonal impressions than they might convey in synchronous CMC or face-to-face communication [87]. Students can take advantage of the time delay inherent in the asynchronous CMC systems to reflect and compose coherent responses [60,88]. A study on the use of e-mail in a reading education class [89] has shown that reflective thinking does occur among students in e-mail interactions.…”
Section: Time Delaymentioning
confidence: 97%
“…Software can be used to construct an ideal leadership structure and an environment for interaction [22,59]. Instructors can take advantage of the several threads of communication that develop in student comments, as on the bulletin board, to direct and organize the discussion [60]. Paulsen [61] argued that e-mail could support a number of learning techniques, such as learning contracts, mentorship and apprenticeship, and correspondence study to increase interactions.…”
Section: Access-availabilitymentioning
confidence: 99%
“…The fact that text-based, asynchronous CSCL may proceed in parallel discussion threads may support participation, because production blocking effects are being reduced. Learners can elaborate their contributions without interruptions from co-present peers, which may suggest to write longer and more elaborated messages (Kern, 1995;Quinn, Mehan, Levin, & Black, 1983).…”
Section: Participation Dimensionmentioning
confidence: 99%